Quo Vadis Higher Order Thinking Skills (HOTS) pada Soal UM-PTKIN Materi Pendidikan Agama Islam - Huriyah, Lilik; Fahmi, Muhammad; Baru, Rohaizan; Ilaihi, Wahyu (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2020)
Human resource input in higher education is required to have high order thinking skills (HOTS) which includes the ability to analyze, evaluate and create material. Thus, the existence of the college entrance test is one of the important instruments in selecting human resources. This article aims to explore the HOTS map on the Entrance Examination for State Islamic Religious Higher Education (UM-PTKIN) in the material of Islamic Religious Education (PAI) in 2018 and the comparison of HOTS levels in the PAI material group examination. This article is also supported by the results of a literature review. The results of the study show that the UM-PTKIN item on PAI material spreads in the HOTS category and low-level thinking skills (LOTS). Akidah Akhlak Subject is the largest contributor and Al-Quran-Hadith as the lowest contributor to the HOTS category questions. The Islamic Religious Education Study Program (PAI) is a study program that is in great demand and its graduates are highly awaited to be able to sow Islamic understanding to answer various social, political and religious challenges in Indonesia. This article provides recommendations for UM-PTKIN policy makers to be able to increase the number of HOTS question compositions in subsequent selections in order to improve the quality of PAI student input in the following periods.